Design and development of remote‐control system for two‐wheel paddy transplanter. Issue 3 (8th November 2021) - Lohan, Shiv Kumar; Narang, Mahesh Kumar; Singh, Manjeet; Singh, Derminder; Sidhu, H. S.; Singh, Sukhmeet; Dixit, Anoop Kumar; Karkee, Manoj
Abstract: To reduce the human effort involved in walk‐behind paddy transplanter operation, a remote‐control system consisting of an electronic control unit (ECU) was designed and developed. A separate remote handheld wireless kit was developed to control the ECU. The deviation from a straight‐line path was measured by mounting a real‐time kinematic global satellite navigation system on the transplanter to provide a real‐time plot of the navigation path of the transplanter. The results from the field evaluation revealed that the system worked properly with an effective field capacity of 0.16 ± 0.03 ha h −1 with a field efficiency of 73.05% ± 0.35% at 1.8 km h −1 in sandy loam soil. The mean deviation from the predefined straight path was 0.227 ± 0.041 m for the remote‐controlled transplanter as compared to 0.171 ± 0.041 m for a manually operated transplanter. The net benefit of using the transplanter with the developed system was $40 per hectare and $2084 per year with a payback period of 2.7 years. The developed remote‐control system reduced the drudgery/fatigue by up to 90% and increased the operator's work efficiency. In addition, an operator sitting in a safe and comfortable environment outside the puddled field improved the field capacity of paddy transplanters by up to 10% and helped minimize the effects of labor shortage during the transplanting season.